Intervensi keperawatan untuk mengatasi kecemasan anak pada fase pemulihan pascabencana - Gustiani, Ajeng; Ariestanti, Nurrachma; Izzany, Raden Maghfira; Nurani, Rai; Safitri, Helni Yusriya; Situmorang, Gantiar Marsaulina; Nuraeni, Aan; Trisyani, Yanny (Holistik Jurnal Kesehatan, 2025)
Background: Children are the most vulnerable group to the impacts of disasters, including disruptions to their physical and mental health. A common psychological effect is anxiety, which can develop into post-traumatic stress disorder (PTSD), depression, and prolonged trauma. Nurses play a crucial role in providing interventions to help reduce post-disaster anxiety in children. Purpose: Identify and explore nursing interventions that have been proven effective in reducing anxiety among children in post-disaster situations. Method: A scoping review method following the PCC (Population, Concept, Context) framework. Literature searches were conducted in the PubMed, Scopus, EBSCOhost, and Science Direct databases, covering publications from 2015 to 2025. Only experimental study designs (Randomized Controlled Trials and quasi-experimental studies) focusing on nursing interventions for post-disaster anxiety in children were included. Articles were selected using PRISMA guidelines and assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Results: 8,114 identified articles, seven met the inclusion criteria and were further analyzed. The findings indicate that various nursing interventions effectively reduce post-disaster anxiety in children, including Cognitive Behavioral Therapy (CBT), Trauma-Focused CBT (TF-CBT), thought-stopping therapy, Eye Movement Desensitization and Reprocessing (EMDR), technology-based interventions (Bounce Back Now), and micronutrient supplementation. Studies suggest that technology-based and brief interventions can reach a wider population at a lower cost, while nutrition-based interventions provide additional benefits in reducing anxiety and improving psychosocial functioning. Conclusion: Nursing interventions such as CBT, technology-based approaches, and micronutrient supplementation are effective in managing post-disaster anxiety in children. Additionally, micronutrient supplementation can serve as a complementary intervention to support children's recovery.   Keywords: Anxiety; Children; Nursing Interventions; Post-Disaster.   Pendahuluan: Anak merupakan kelompok paling rentan terhadap dampak bencana, termasuk gangguan kesehatan fisik dan mental. Dampak psikologis yang sering terjadi adalah kecemasan, yang dapat berkembang menjadi gangguan stres pasca trauma (PTSD), depresi, dan trauma berkepanjangan. Perawat memiliki peran penting dalam memberikan intervensi yang dapat membantu mengurangi kecemasan anak pascabencana. Tujuan: Untuk mengidentifikasi dan mengeksplorasi intervensi keperawatan yang telah terbukti efektif dalam mengurangi kecemasan pada anak-anak pascabencana. Metode: Scoping review dengan mengikuti kerangka kerja PCC (Population, Concept, Context). Pencarian literatur dilakukan di database PubMed, Scopus, EBSCOhost, dan Science Direct dengan rentang tahun 2015–2025. Hanya artikel dengan desain penelitian eksperimental (Randomized Controlled Trial dan quasi-eksperimental) yang berfokus pada intervensi keperawatan dalam mengatasi kecemasan anak pascabencana. Artikel diseleksi menggunakan pedoman PRISMA dan dinilai menggunakan Joanna Briggs Institute (JBI) Critical Appraisal Tools. Hasil: Sebanyak 8,114 artikel yang diidentifikasi, 7 artikel memenuhi kriteria inklusi dan dianalisis lebih lanjut. Berbagai intervensi keperawatan efektif dalam mengurangi kecemasan anak pascabencana, termasuk terapi kognitif perilaku (CBT), trauma-focused CBT (TF-CBT), terapi penghenti pikiran, desensitisasi gerakan mata dan pemrosesan ulang (EMDR), intervensi berbasis teknologi (Bounce Back Now), serta suplementasi mikronutrien. Studi menunjukkan intervensi berbasis teknologi dan terapi singkat dapat menjangkau populasi yang lebih luas dengan biaya lebih rendah, sementara intervensi berbasis nutrisi memberikan manfaat tambahan dalam mengurangi kecemasan dan meningkatkan fungsi psikososial. Simpulan: Intervensi keperawatan seperti CBT, teknologi, dan suplementasi mikronutrien efektif mengatasi kecemasan anak pascabencana. Selain itu, suplementasi mikronutrien dapat digunakan sebagai intervensi tambahan untuk mendukung pemulihan anak.   Kata Kunci: Anak-anak; Intervensi Keperawatan; Kecemasan; Pascabencana.